Globalizacija, gospodarska in socialna kriza - Svetlik, Ivan (Teorija in praksa, 2014)
In the article we assume that globalisation is an irreversible process associated with the profound structural changes in the economic and social tissue of contemporary societies. Its main characteristic is proliferation of the world markets of capital, goods and labour which have been enabled by new information and communication technologies and enhanced by the inadequate distribution of incomes between labour and capital and by financialisation. In the developed countries we can observe slow down of economic growth, loss of jobs and a strong pressure exerted on living standard and welfare state. In the developing countries economic growth and entry of millions of people in economic activities and consumption is evident. The focus of conflict has been shifted from the relation between less and more developed countries to the relation between social classes. The conflict could be solved rather by means of globalisation of labour than by de-globalisation. In spite of global market pressures small countries, such as Slovenia, could find ways of prosperity.
Keywords: Economic crisis (2008); ekonomska kriza; Employment; Globalizacija; Globalization; Gospodarska kriza (2008); Zaposlovanje